Serpiginous Choroiditis with Atypical Presentation Treated with Intravenous Methyl Prednisolone. (March 2015) - Balakrishnan, Divya; Mathai, Annie; Gogte, Priyanka; Tibra, Nandkishore; Chhablani, Jay
Abstract Purpose: The purpose of this study is to report a case of atypical serpiginous choroiditis presenting with disc edema and exudative retinal detachment, treated successfully with intravenous methyl prednisolone. Methods: A 45-year-old male patient presented with sudden decrease of vision in his left eye. On examination, left eye showed disc edema, exudative retinal detachment, and active serpiginous choroiditis. He was treated with intravenous methyl prednisolone followed by oral steroids and Azathioprine. Results: At six weeks of follow-up, the choroiditis resolved completely with improvement of visual acuity. Conclusion: Atypical presentations of serpiginous choroiditis can cause diagnostic dilemma, but prompt diagnosis and immediate treatment can result in good visual recovery.